Bimbingan Teknik Penulisan Artikel Pengabdian Dan Penelitian Dosen Homebase Sekolah Tinggi Ilmu Tarbiyah Hidayatullah Batam Kepulauan Riau - Muthmainnah; Mohammad Ramli; Frangky Silitonga (PUSLITABMAS-Politeknik Pariwisata Batamc, 2023)
The technical assistance activity for writing articles Homebase Lecturer Service and Research at the Tarbiyah Hidayatullah Batam Kepulauan Riau (STIT. Hidayatullah Batam Kepulauan Riau) College of Science is a collaborative service activity between the Batam Tourism Polytechnic and STIT. Hidayatullah Batam Kepulauan Riau. The target achievement of this activity is to be able to create a means of publishing scientific papers from the results of OJS-based research and service. This journal uses the V.3.3 type of PKP. So far STIT. Hidayatullah Batam Kepulauan Riau itself has had a journal to publish the results of research and dedication of lecturers and students in print and online form since 2022. Where the means of publication in mid-2022 are Tadribuna: Journal of Islamic Education Management and Ta'diban: Journal of Islamic Education. Both of these journals focus publications on research results. In this activity, the servant collaborated between the STIT. Hidayatullah Batam Kepulauan Riau institution and the Batam Tourism Polytechnic, the method of community service activities was carried out face to face and Virtual meetings using a live meeting-based information system to accelerate finding solutions and priority scale OJS-based journal publications at STIT. Hidayatullah Batam Kepulauan Riau. The method approach used is lectures, role play and demonstrative as well as direct practice in live meetings using zoom meetings that have been scheduled regularly and in a structured manner. The results obtained are participants are able to register at OJS as writers, can submit articles, then become part of the editorial board and can play a role in the regular and measurable OJS management process before the articles are published until the articles will be published by OJS. The limitations of long distances, time and instruments used during mentoring activities for community service activities can be minimized with the support of internet access technology that is quite good, the enthusiasm of the activity participants and a family atmosphere to jointly advance STIT. Hidayatullah Batam Kepulauan Riau.